Close Reading and Movement: A Lesson on Student Engagement and the Four Cs (LEARNing Landscapes, 2016)
Close reading is a reading instruction strategy. The author combined movement with close reading to engage fourth-grade students in meaning-making of new academic vocabulary words. Through the experience, students assessed new and multiple meanings of words and participated in collaborative, academic discussions of vocabulary words using human sculptures. Findings from the lesson suggest: an increase in student interest in vocabulary development when combined with movement, an instructional method that made sense to students, and a nonthreatening way to engage English learners in text-dependent inquiries. Future investigations may explore the lesson’s feasibility with students in the middle and secondary grades.
Keywords: engagement; close reading; movement; instruction; sculpting